MicroRNA-645 targets urokinase plasminogen activator and decreases the invasive growth of MDA-MB-231 triple-negative breast cancer cells - Meng, Du (Onco Targets Ther, 2018)
BACKGROUND: Urokinase plasminogen activator (uPA) promotes the in vivo invasive growth of HCC cells by cleaving and activating matrix metalloproteinases (MMPs) to induce the destruction of the extracellular matrix of triple-negative breast cancer (TNBC) cells. The identification of microRNAs that target uPA and decrease uPA expression would be useful for attenuating the in vivo invasive growth of TNBC cells. MATERIALS AND METHODS: MicroRNA-645 (miR-645) was identified using an online tool (miRDB) as potentially targeting uPA; miR-645 inhibition of uPA was confirmed by western blot experiments. The effects of miR-645 on the in vivo invasive growth of TNBC cells were examined using an intrahepatic tumor model in nude mice, and the miR-645 mechanism of action was explored with MMP cleaving experiments. RESULTS: Through virtual screening, we discovered that miR-645 potentially targeted the uPA 3′ untranslated region. This targeting was confirmed by western blot experiments and miR-645 lentiviral particle (LV-645) transduction that inhibited uPA expression in MDA-MB-231 TNBC cells. The LV-645 inhibition of uPA led to the decreased invasive growth of TNBC cells in nude mice. The mechanism data indicated that the uPA inhibition resulted in a decreased cleaving of the pro-MMP-9 protein. CONCLUSION: Targeting uPA with miR-645 decreased the in vivo invasive growth of TNBC cells. These results suggest that miR-645 may represent a promising treatment strategy for TNBC.